Hydrated Lime Soil Coverage: Effect On Soil Temperature Reduction And Early Mandarin Colour Break - Gambetta, Giuliana; Mesejo, Carlos; Gravina, Alfredo; Agustí, Manuel; Fasiolo, Carolina; Rey, Florencia; Reig, Carmina; Martínez-Fuentes, Amparo; Bentancur, Oscar (Agrociencia Uruguay, 2015)
Citrus fruit colour is an important marketing feature. In view of the relative independence between internal and external maturity, in early mandarins fruit harvest takes place before reaching fruit full colouration. Since citrus fruit colour break is associated to natural temperature reduction, this work evaluated the efficiency of hydrated lime soil coverage on the advance of fruit colour break of Satsuma and Clementine. Experiments were carried out in Spain (Satsuma 'Iwasaki' and Clementina 'Clemenpons', grafted on citrange 'Carrizo') and in Uruguay (Satsuma 'Okitsu' and 'Clementina de Nules', grafted on P. trifoliata). Hydrated lime was applied between two and four months before harvest. Treatment diminished soil temperature between 0.5 °C and 3 °C in all situations. In Satsuma, treatment could not advance colour break, since soil temperature remained above 23 °C and 18 °C, thresholds below which root metabolism of citrange 'Carrizo' and P. trifoliata, respectively, is reduced. In Clementine, maturing two months later, the soil temperature remained below thresholds during at least one month before harvest, significan-tly advancing fruit colour break and increasing the percentage of fruit harvested early.